PENERAPAN BAHASA JURNALISTIK PADA BERITA KRIMINAL - firdaus, kharisma arrifal; Sumadiria, Hari; Muslim, Acep (Annaba: Jurnal Ilmu Jurnalistik, 2021)
This study aims to identify the application of populist journalistic language (familiar to the reader's ears, in the eyes, and in the mind), (effective, practical, and easy to understand), identify the application of journalistic language avoiding foreign words and terms (informative, communicative, and not confusing) on crime news. The concept used is 17 characteristics of journalistic language, (Sumadiria, 2010: 14-20). This study uses a content analysis method, in this study describe in detail about a research subject. Researchers can carry out an analysis regarding the application of populist journalistic language (familiar to the ear, in the eyes, and in the minds of readers), simple (effective, practical, and easy to understand), (informative, communicative, and not confusing) in Radarbandung.id crime news edition May 01-June 01 2022.